2006
DOI: 10.1016/j.lfs.2006.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of soluble epoxide hydrolase reduces LPS-induced thermal hyperalgesia and mechanical allodynia in a rat model of inflammatory pain

Abstract: Soluble epoxide hydrolases catalyze the hydrolysis of epoxides in acyclic systems. In man this enzyme is the product of a single copy gene (EPXH-2) present on chromosome 8. The human sEH is of interest due to emerging roles of its endogenous substrates, epoxygenated fatty acids, in inflammation and hypertension. One of the consequences of inhibiting sEH in rodent inflammation models is a profound decrease in the production of pro-inflammatory and proalgesic lipid metabolites including prostaglandins. This prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
191
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(205 citation statements)
references
References 45 publications
10
191
4
Order By: Relevance
“…In mice during sepsis or in rats during local inflammation, increased plasma PGE 2 levels were consistently reduced after sEHI treatment (13,15). However, peripheral inflammation and noxious stimuli are known to evoke a robust increase in the spinal cord COX2 gene expression and prostanoid production (17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice during sepsis or in rats during local inflammation, increased plasma PGE 2 levels were consistently reduced after sEHI treatment (13,15). However, peripheral inflammation and noxious stimuli are known to evoke a robust increase in the spinal cord COX2 gene expression and prostanoid production (17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…However, EETs are stabilized by using inhibitors of sEH (sEHI) that prevent the conversion of EETs to corresponding diols (7). The increased EETs then lead to a reduction in blood pressure during hypertension and to antihyperalgesia during inflammation whereas the diols are thought to be less active (7,13,14). Although many in vitro biological activities of EETs are characterized, the ability to inhibit sEH in vivo provides the advantage of revealing the systemic physiological effects of these molecules.…”
mentioning
confidence: 99%
“…In these studies, nbAUDA was effective in attenuating cisplatin-induced renal injury; the protective effect of AUDA was marginal and highly variable (data not shown). Although both AUDA and its butyl ester have been found to be effective in vivo in other systems (Smith et al 2005;Schmelzer et al 2005;Liu et al 2005;Inceoglu et al 2006;Schmelzer et al 2006;Xu et al 2006), it is not surprising that the free acid is less effective under conditions where it needs to be continually available to protect the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…sEH inhibitors have been shown to normalize blood pressure in spontaneously hypertensive rats (Yu et al 2000) and in rats challenged with angiotensin (Imig et al 2002). Furthermore, the sEH inhibitors have been found to be strongly antiinflammatory in several in vivo bioassays (Smith et al 2005;Schmelzer et al 2005;Liu et al 2005;Inceoglu et al 2006;Schmelzer et al 2006;Xu et al 2006). Arachidonic acid epoxides [epoxyeicosatrienoic acids (EETs)] are endogenous regulators that influence inflammation (Node et al 1999) and blood pressure (Roman 2002) in the kidney; both inflammation and renal blood flow are critical mediators of cisplatin-mediated acute kidney injury (Jo et al 2005;Winston and Safirstein 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that EETs inhibit the stimulation of the transcription factor nuclear factor to produce their vascular anti‐inflammatory responses 15, 16. Studies using inhibitors of soluble epoxide hydrolase (sEH) also support the idea that EETs have anti‐inflammatory actions 17, 18. Based on these findings, inhibitors of sEH could be protective against the detrimental effects of inflammation that occur in cardiovascular diseases and that they could afford cure for other inflammatory diseases 19.…”
Section: Discussionmentioning
confidence: 99%